The Effects of Acute Hydrogen Sulfide Poisoning on Cytochrome P450 Isoforms Activity in Rats. (25th March 2014) - Wang, Xianqin; Chen, Mengchun; Chen, Xinxin; Ma, Jianshe; Wen, Congcong; Pan, Jianchun; Hu, Lufeng; Lin, Guanyang
Abstract : Hydrogen sulfide (H2 S) is the second leading cause of toxin related death (after carbon monoxide) in the workplace. H2 S is absorbed by the upper respiratory tract mucosa, and it causes histotoxic hypoxemia and respiratory depression. Cocktail method was used to evaluate the influences of acute H2 S poisoning on the activities of cytochrome P450 isoforms CYP2B6, CYP2D6, CYP3A4, CYP1A2, CYP2C19, and CYP2C9, which were reflected by the changes of pharmacokinetic parameters of six specific probe drugs, bupropion, metoprolol, midazolam, phenacetin, omeprazole, and tolbutamide, respectively. The experimental rats were randomly divided into two groups, control group and acute H2 S poisoning group (inhaling 300 ppm for 2 h). The mixture of six probes was given to rats by oral administration and the blood samples were obtained at a series of time points through the caudal vein. The concentrations of probe drugs in rat plasma were measured by LC-MS. The results for acute H2 S poisoning and control groups were as follows: there was a statistically significant difference in the AUC and C max for bupropion, metoprolol, phenacetin, and tolbutamide, while there was no statistical pharmacokinetic difference for midazolam and omeprazole. Acute H2 S poisoning could inhibit the activity of CYP2B6, CYP2D6, CYP1A2, and CYP2C9 in rats.